P. Vellei Patercvli Historiae Romanae dvo volvmina, ad M. Vinicivm Cos. progenervm Tiberii caesaris - Velleius Paterculus, Caius, ca. 19 B.C.-ca. 30 A.D.; Frobenius, Joannes, 1491-1527; Holbein, Ambrosius, 1494?-1518?; Holbein, Hans, de Jongere, ca. 1497-1543; Rhenanus, Beatus, 1485-1547 (Basileae : in aedibvs Ioannis Frobenii, 1520)
The author, Paterculus, wrote the book in two volumes, some of which did not survive. The first volume strays from typical Roman historical texts since it included events which did not simply focus on Rome but on the rest of the ancient world. Rhenanus, the redactor, found an original but corrupted manuscript in a monastary in 1515, and gave the work its present title, which focuses on just the Roman aspects of the author's history.
Impressum uit colofon: mense Novembri
The printing devices were designed by Ambrosius and Hans Holbein based on the Hieroglyphica of Horapollo.
Title within borders of Ambrosius and Hans Holbein, who also cut the second border on preliminary leaf 2 and p. 1., and the head pieces and initials.
Keywords: Rome -- History -- Early works to 1800.